METAMORFOSIS INSTITUSI PENDIDIKAN ISLAM DI INDONESIA - Abubakar, Isti’anah (J-PAI: Jurnal Pendidikan Agama Islam, 2017)
The study of the history of Islamic education in Indonesia is a study that should continue to be able to give ibrah for development and improvement of the quality of education. This dynamics is the metamorphosis, a process towards perfection. Based on a historical perspective, Islamic educational institution found that Indonesia is still experiencing a metamorphosis is less perfect. This indicates that the Islamic educational institutions should hold first settled towards perfect metamorphosis, a process that ushers in the institution of Islamic institutions on excellence and advancement. This paper attempts, identify the metamorphosis of the Islamic educational institutions as well as find aspects of the imperfections of the process metamorfosisnya. The results of this paper will, be insightful while discourse and early action to improve the image and quality of the institutions of Islam.